Manual Distractions of Ambulance Drivers: Light-and-siren vs. Non-light-and-siren Travel. (September 2014) - Grundgeiger, T.; Scharf, M.; Grundgeiger, J.; Scheuchenpflug, R.
Emergency medical services personnel are involved in more transportation accidents and have higher fatality rates than do other professions, and traveling with light-and-siren is particularly risky. One factor that might contribute to transportation accidents is driver distraction. We investigated what kind of manual secondary tasks – distractions that require the driver to take at least one hand off the steering wheel – ambulance drivers face and compared the relative frequency and proportion of time spent in manual operations not related to driving for light-and-siren travel vs. non-light-and-siren travel. The results indicate that ambulance drivers face more manual distractions when traveling with light-and-siren than non-light-and-siren. In particular, operating the light-and-siren system is causing most of the manual distractions. We discuss the results and potential implication for practice.